Cerebro‐placental and umbilico‐cerebral ratios in uncomplicated monochorionic twins: Longitudinal references and comparison with singletons. (5th August 2022) - Casati, Daniela; Zavatta, Alice; Cortinovis, Ivan; Spada, Elena; Faiola, Stefano; Laoreti, Arianna; Cetin, Irene; Lanna, Mariano
Abstract: Objectives: Monochorionic twins (MC) are at high risk of adverse outcomes and Doppler investigation of umbilical and cerebral flows is mandatory for their surveillance. The cerebro‐placental (CPR) and umbilico‐cerebral (UCR) ratios are considered non‐invasive measures of fetal adaptation to hypoxemia. We aimed to provide longitudinal references for CPR and UCR from 16 to 37 weeks of gestation that are specific for MC twins, and compare these with singleton charts. Methods: Longitudinal study of a cohort of consecutive uncomplicated MC twin pregnancies monitored at our unit from 2010 to 2018. The estimated centile curves were obtained estimating the median with fractional polynomials by a multilevel model and the external centiles through the residuals. The comparison with singletons references was made through graphic evaluation. Results: One‐hundred‐fifty‐two MC pregnancies were included with a median of 10 longitudinal ultrasounds each. References for CPR and UCR in function of gestational age are presented. Compared to singletons, MC twins showed an earlier and greater circulatory redistribution with lower CPR and higher UCR median values. Conclusions: MC twin‐specific references for CPR and UCR suitable for serial monitoring are presented. The comparison with singleton references demonstrates substantial differences in the hemodynamic balance that must be considered when interpreting findings in MC twins. Key points: What's already known about this topic? Uncomplicated monochorionic twins have higher umbilical flow and lower cerebral flow resistances compared to singletons, especially at increasing gestational ages. What does this study add? Monochorionic twins‐specific longitudinal references for cerebro‐placental and umbilico‐cerebral ratios from 16 to 37 weeks are reported. Compared to singletons, uncomplicated monochorionic twins exhibit earlier and greater centralization of blood flow.